2016
DOI: 10.1002/ece3.2384
|View full text |Cite
|
Sign up to set email alerts
|

The role of novel forest ecosystems in the conservation of wood‐inhabiting fungi in boreal broadleaved forests

Abstract: The increasing human impact on the earth's biosphere is inflicting changes at all spatial scales. As well as deterioration and fragmentation of natural biological systems, these changes also led to other, unprecedented effects and emergence of novel habitats. In boreal zone, intensive forest management has negatively impacted a multitude of deadwood‐associated species. This is especially alarming given the important role wood‐inhabiting fungi have in the natural decay processes. In the boreal zone, natural bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…However, the dead wood profile does not seem to be the only determining factor explaining the differences in fungal communities among different forest types. For example, previously (Juutilainen et al 2016) we found that the dead wood profile did not explain why the fungal species richness and the number of rare species was relatively high in afforested fields compared to other habitats, even though the amount and diversity of dead wood in the afforested fields is very limited.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…However, the dead wood profile does not seem to be the only determining factor explaining the differences in fungal communities among different forest types. For example, previously (Juutilainen et al 2016) we found that the dead wood profile did not explain why the fungal species richness and the number of rare species was relatively high in afforested fields compared to other habitats, even though the amount and diversity of dead wood in the afforested fields is very limited.…”
Section: Discussionmentioning
confidence: 64%
“…insperata, which was one of the most abundant species in afforested fields, but absent from every other forest type. This species was practically always found on small diameter birch wood (only one additional observation from unidentified deciduous wood), a substratum very common in all the deciduous forest types (Juutilainen et al 2016) and also present in all coniferous forests (Juutilainen et al 2014). It seems that some unknown factors play an additional role in the habitat selection of this and of other similar species.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations